Screening and Genetic Network Analysis of Genes Involved in Freezing and Thawing Resistance in DaMDHAR—Expressing Saccharomyces cerevisiae Using Gene Expression Profiling - Il-Sup Kim; Woong Choi; Jonghyeon Son; Jun Hyuck Lee; Hyoungseok Lee; Jungeun Lee; Seung Chul Shin; Han-Woo Kim (Genes, 2021)
The cryoprotection of cell activity is a key determinant in frozen-dough technology. Although several factors that contribute to freezing tolerance have been reported, the mechanism underlying the manner in which yeast cells respond to freezing and thawing (FT) stress is not well established. Therefore, the present study demonstrated the relationship between DaMDHAR encoding monodehydroascorbate reductase from Antarctic hairgrass Deschampsia antarctica and stress tolerance to repeated FT cycles (FT2) in transgenic yeast Saccharomyces cerevisiae. DaMDHAR-expressing yeast (DM) cells identified by immunoblotting analysis showed high tolerance to FT stress conditions, thereby causing lower damage for yeast cells than wild-type (WT) cells with empty vector alone. To detect FT2 tolerance-associated genes, 3′-quant RNA sequencing was employed using mRNA isolated from DM and WT cells exposed to FT (FT2) conditions. Approximately 332 genes showed ≥2-fold changes in DM cells and were classified into various groups according to their gene expression. The expressions of the changed genes were further confirmed using western blot analysis and biochemical assay. The upregulated expression of 197 genes was associated with pentose phosphate pathway, NADP metabolic process, metal ion homeostasis, sulfate assimilation, β-alanine metabolism, glycerol synthesis, and integral component of mitochondrial and plasma membrane (PM) in DM cells under FT2 stress, whereas the expression of the remaining 135 genes was partially related to protein processing, selenocompound metabolism, cell cycle arrest, oxidative phosphorylation, and α-glucoside transport under the same condition. With regard to transcription factors in DM cells, MSN4 and CIN5 were activated, but MSN2 and MGA1 were not. Regarding antioxidant systems and protein kinases in DM cells under FT stress, CTT1, GTO, GEX1, and YOL024W were upregulated, whereas AIF1, COX2, and TRX3 were not. Gene activation represented by transcription factors and enzymatic antioxidants appears to be ...